Acute bacterial prostatitis in an adolescent patient following blunt trauma. Issue 1 (2nd January 2018) - Wolfe, Taylor; Smith, Cynthia; Jacob, Roy
ABSTRACT: Acute bacterial prostatitis is a common disease among adults. Acute bacterial prostatitis in the pediatric population is rare with only a few case reports in the literature. This case highlights an unusual presentation of prostatitis in a 16-year-old who presented with suprapubic pain and hematuria following blunt trauma to the lower abdomen.